Effect of a Scale‐Aware Convective Parameterization Scheme on the Simulation of Convective Cells‐Related Heavy Rainfall in South Korea. (30th May 2022) - Park, Haerin; Kim, Gayoung; Cha, Dong‐Hyun; Chang, Eun‐Chul; Kim, Joowan; Park, Sang‐Hun; Lee, Dong‐Kyou
Abstract: In this study, the effect of a scale‐aware convective parameterization scheme (CPS) on the simulation of heavy precipitation in the gray‐zone was investigated using the Weather Research and Forecasting (WRF) model. We performed WRF simulations with the Kain–Fritsch (KF) scheme (non‐scale‐aware), Multiscale Kain–Fritsch (MSKF) scheme (scale‐aware), and explicit convection (i.e., no CPS). The MSKF scheme uses a scale‐aware parameter that modulates the convective available potential energy (CAPE) timescale and entrainment process in the KF scheme as a function of the horizontal grid spacing. The results of this study show that WRF simulations using explicitly resolved convection lead to overestimations and erroneous precipitation locations in the gray‐zone because the convection and atmospheric instability cannot be appropriately triggered and reduced. The CPS without scale‐awareness in the gray‐zone exaggerates the convection and distorts synoptic fields, leading to the erroneous simulation of heavy precipitation at high resolution. The MSKF scheme with scale‐awareness improves the simulation of convective cells‐related heavy rainfall by removing the atmospheric instability in the gray‐zone, reducing the role of the CPS, and increasing the role of the microphysics parameterization scheme (MPS) with decreasing grid spacing. In addition, the results of sensitivity experiments show that reducing the CAPE timescale leads to the faster development of convective cells, whereas decreasing the entrainment leads to precipitation overestimation. The modulated parameters in the scale‐aware MSKF scheme play a crucial role in balancing the effects of the CPS and MPS in the gray‐zone. Plain Language Summary: Based on the increase in computational resources, numerical weather prediction models are operating in the "gray‐zone" for horizontal grid spacing in the range of 1–10 km in which both cumulus parameterizations and explicitly resolved deep convection are problematic. In this study, the effect of the scale‐aware convective parameterization scheme (CPS) on the simulation of convective cell‐related heavy precipitation across the gray‐zone was investigated using the Weather Research and Forecasting (WRF) model. The scale‐aware CPS uses a scale‐aware parameter, which modulates the convective process as a function of the horizontal grid spacing. We found that simulating convection processes in the gray‐zone without the CPS is inadequate. Furthermore, the CPS without scale‐awareness generates an erroneous precipitation simulation due to the exaggeration of convection and distortion of synoptic fields. In contrast, the scale‐aware CPS improves the simulation of convection cell‐related heavy rainfall in the gray‐zone by reducing the role of the CPS and increasing that of explicitly resolved precipitation with the decrease in the grid spacing. Our results indicate that using a scale‐aware CPS and managing convective processes are crucial in controlling the CPS and microphysics parameterization scheme (MPS) in the gray‐zone. Key Points: We investigated the impact of the scale‐aware convective parameterization scheme (CPS) across the gray‐zone using the Weather Research and Forecasting model The scale‐aware CPS improved simulated convective cells related to rainfall by properly removing atmospheric instability in the gray‐zone Convective available potential energy timescale and entrainment rate modulated in the Multiscale Kain–Fritsch are the key parameters for the improved rainfall simulation in the gray‐zone